2018
DOI: 10.33899/mmed.2018.160002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo biloba on lipid profile in hypertensive patients on Valsartan monotherapy

Abstract: Aim:The study was conducted to evaluate the effects of Ginkgo biloba as an add on therapy to Valsartan monotherapy in hypertensive patients on lipid profile. Patients and methods:The study was done in private clinics in Mosul City, during a period of sixth months from 15 October 2017 to 15 April 2018. The total number of patients enrolled in the study was 50 hypertensive patients using Valsartan monotherapy of both sexes. The patients were administered Ginkgo biloba 80 mg twice daily and followed for 2 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, the IC 50 value of UA and orlistat to PL was 1.81 ± 0.13 mg/mL and 0.05 ± 0.02 mg/mL, respectively. Although less compared to orlistat, the inhibition efect of UA on CEase was higher than that of ginkgolide B (IC 50 : 0.34 ± 0.02 mg/mL) [36], as well as that of UA on PL was higher than that of betulin (IC 50 : 3.19 ± 0.11 mg/mL) and ginsenoside Rd (IC 50 : 4.06 ± 1.41 mg/mL) [21].…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, the IC 50 value of UA and orlistat to PL was 1.81 ± 0.13 mg/mL and 0.05 ± 0.02 mg/mL, respectively. Although less compared to orlistat, the inhibition efect of UA on CEase was higher than that of ginkgolide B (IC 50 : 0.34 ± 0.02 mg/mL) [36], as well as that of UA on PL was higher than that of betulin (IC 50 : 3.19 ± 0.11 mg/mL) and ginsenoside Rd (IC 50 : 4.06 ± 1.41 mg/mL) [21].…”
Section: Resultsmentioning
confidence: 85%
“…This observation is consistent with an earlier study that demonstrated the ability of Ginkgo biloba to reduce serum total cholesterol and triglycerides [ 56 ]. Other notable studies showed that GB has an effect on the absorption of triglyceride and cholesterol as well as cholesterol metabolism; a possible explanation for the ability of Ginkgo biloba to lower the level of lipids, and therefore deter the development and progression of artherosclerosis and cardiovascular diseases [ 60 62 ]. These prior studies corroborate findings from the current study that show MelB and GB-driven abrogation of T.b.r-induced elevation of cholesterol and triglycerides as well as depletion of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Also, curcumin can lower total cholesterol, triglycerides and LDL (Lee, 2016), and raising HDL-C, which is associated with lower risk of heart disease. (Qin, 2017 andAl-Zakaria et al, 2018).…”
Section: Discussionmentioning
confidence: 99%